PROPHETIC PARENTING SEBAGAI MODEL PENGASUHAN DALAM PEMBENTUKAN KARAKTER (AKHLAK) ANAK - Yulia Hairina (Jurnal Studia Insania, 2016)
Children are an mandate from Allah to all parents. They must give them a good education in order to be good Muslims and they worship to Allah. Parents are the first teachers who have a responsibility in developing children’s psychology both of spiritual and physical needs. In this case, parents have main position in forming the children’s character. This era, there are children do many deviations more and more. It indicates that there is something lack in model of nurture by the parents. The model of nurture applied by parents to their children determines the children’s character. The model of nurture in characters building had taught by prophets. Allah had delegated all prophets to the world by giving a main mission that is the character building. Islam is present as a movement to complete the human’s character. Islam explains that a good education is the children’s right to their parents. The good education means here is an education based on the Quran and the purposes to build the Muslim personality, who totally allows to the God, by guidance had taught by Prophet Muhammad (pbuh). This writing is aimed at describing education method and concept in progressing character building for children, which had done Prophet Muhammad (pbuh) and it will be related to Psychology.